EFL TEACHERS’ TECHNOLOGY ACCEPTANCE: APPLYING THE TECHNOLOGY ACCEPTANCE MODEL IN SECONDARY LANGUAGE LEARNING IN INDONESIA - Bulan Pangestu; Dwiniasih, Dwiniasih (Cirebon International Conference on Education and Economics Proceeding, 2024)
This study explores the technology acceptance among English as a Foreign Language (EFL) teachers in secondary schools in Cirebon using the Technology Acceptance Model (TAM) introduced by Davis in 1989. The research highlights the perceived usefulness and ease of use of technology in language learning, along with the factors influencing the adoption of technology among EFL teachers. Employing a qualitative research approach, data were collected through a questionnaire adapted from Cox, Preston, and Cox (1999), involving 25 EFL teachers. The findings indicate that positive perceptions of technology increase the likelihood of its use in teaching. However, significant differences were found in technology acceptance between novice and experienced teachers, with novice teachers showing higher levels of acceptance. This study underscores the importance of training and technical support in facilitating effective technology integration in language learning.